Fifteenth century XVII : finding individuality - Clark, Linda (Fifteenth century, 2020)
The essays collected here cast light on the factors that made or defined an individual, and the ways in which the men and women concerned gave expression to their individuality. Facets of the characters of English kings emerge from the varying contents of their wills, and the use of propaganda in their personal letters. By contrast, Margaret of Anjou's early years are explored for the roots of her conduct as queen consort, and how she matched up to contemporary expectations following Henry VI's mental collapse. The law courts and the legal profession provide the stage and cast for several papers: individual lawyers, of dubious integrity and adept at manipulating legal processes in their own interests, provoked the violence that led to their own deaths, while a member of the same profession is shown to have orchestrated civic riots in which he and his neighbours sought to give expression to their own status as they perceived it. Finally, in their frustrated search for justice, strong-minded women asserted their individual rights by taking their grievances to Henry VII's star chamber. Contributors: Linda Clark, Chris Given-Wilson, Anthony Gross, David Grummitt, Samuel Lane, Simon Payling, Alice Raw, Anne F. Sutton, Deborah Youngs